The prokaryotes : a handbook on the biology of bacteria; VOL.5 - Dworkin, Martin.; Ed (Springer, 2006)
The Third Edition of The Prokaryotes, acclaimed as a classic in its field, offers new and updated articles by worldwide experts on taxa of relevance to medicine, ecology and industry. Now includes colour illustration throughout, and a searchable online edition.